PECULIARITIES OF CHRONIC PAIN AND PAIN-RELATED STRESS MARKERS IN PRETERM INFANTS - Г. Павлишин; І Сарапук; К. Козак; Т. Зайцева (Bukovynian State Medical University, 2023)
Preterm infants are a special cohort of newborns that require long-term treatment in the neonatal intensive care unit (NICU). NICU stay, accompanied by numerous excessive stimuli, painful procedures, and separation from parents leads to a high risk of chronic pain and stress. The aim of research was to study the level of chronic pain and pain-related stress markers in preterm infants with a gestational age of less than 34 weeks, and their associations with various factors. Materials and methods. The study involved 104 preterm infants with gestational age (GA) less than 34 weeks who were treated in the NICU. The level of chronic pain and pain-related stress markers (dopamine, β-endorphin, serotonin) in urine samples was determined by an enzyme-linked immunosorbent assay using kits for the quantitative determination of dopamine (Dopamine Elisa kit, Elabscience, Wuhan, China), β-endorphin (β-endorphin Elisa kit, Elabscience, Wuhan, China), serotonin (Serotonin Elisa kit, Elabscience, Wuhan, China). Samples were analyzed in duplicate, and assays were performed using provided controls according to the manufacturer's instructions. Ethics approval was obtained from the appropriate local ethics committee and research was conducted under the World Medical Association's Helsinki Declaration. Informed consent was obtained from all the participants who took part in the study. All computations were performed using StatSoft STATISTICA Version 13 (Tulsa, OK). Quantitative data are presented as the median and interquartile range (IQR; 25th to 75th percentiles). For qualitative parameters, absolute and relative frequencies are presented. The Mann-Whitney U-test (for two independent groups) and Kruskal-Wallis test (for three groups) were used to compare numerical data. Significance was assumed at p<0.05. Correlations were analyzed using Spearman's rank correlation coefficient. The study is a part of the scientific research: Implementation of the neuro-developmental care elements for preterm infants and their follow-up observation (0120U104281, 01.01.2020-12.31.2022). Research results and their discussion. Dopamine level in the urine of preterm infants was 132.20 [104.80; 183.70] pg/ml. It was significantly higher in children who underwent mechanical ventilation compared to non-ventilated neonates (164.60 [110.00; 253.70] pg/mL vs. 123.20 [98.65; 158.70] pg /ml), p=0.030, and was associated with the severity of respiratory disorders (H=5.84; p=0.049). Dopamine level was significantly lower in twins compared to singleton infants (113.70 [78.75; 164.70] vs. 145.10 [111.80; 208.50], p=0.017. β-endorphin level in the urine of preterm newborns was 29.87 [20.61; 46.94] pg/ml. It was significantly higher in twins compared to singletons (38.30 21.97; 59.61] vs. 27.80 [19.66; 39.16], p=0.046). β-endorphin level was significantly lower in children with neonatal seizures (p=0.039). Serotonin level in the urine of preterm infants was 23.49 [16.13; 32.19] pg/ml. It was significantly higher in neonates born by caesarean section compared to those born naturally (25.62 [18.87; 38.53] ng/ml vs. 17.41 [13.36; 27.89] ng/ml, p=0.017), and it was higher in twins compared to singletons (27.19 [18.87; 41.75] ng/ml vs. 21.98 [14.41; 29.70] ng/ml), however, with no statistical significance (р=0.073). The study revealed the positive correlation between serotonin and β-endorphin levels (r=0.68; p<0.001) in infants who required mechanical ventilation and in newborns with neonatal seizures (r=0.59; p<0.001). Positive correlation between β-endorphin and serotonin levels in twins also was found (r=0.72, p<0.001). Conclusion. This prospective cohort study showed that severe respiratory disorders in preterm infants were associated with decreased dopamine level, while serotonin and β-endorphin levels were correlated in this case. Neonatal seizures were associated with decreased β-endorphin level, while a positive correlation was found between β-endorphin and serotonin levels. Dopamine levels were significantly lower and β-endorphin levels significantly higher in twins compared to singleton preterm neonates. Serotonin level was significantly higher in neonates born by caesarean section. Gestational age, birth weight, gender, early-onset sepsis, and intraventricular hemorrhage were not associated with increased or decreased levels of pain and pain-related stress markers in preterm infants.